Strategi Pengajaran Geguritan melalui Metode Komunikatif Berbantuan Media Tembang Dolanan Cublak-Cublak Suweng - Muhammad Rifky Saputra (Nexus Publishing, 2024)
This conceptual design aims to present a teaching strategy for geguritan or modern Javanese poetry which contains the meaning, characteristics, types and structure using communicative methods or approaches that prioritize aspects of direct interaction and communication using media or intermediaries of dolanan songs or traditional Javanese songs. suweng, the song has a lot of playing values ​​and teaching values ​​in the form of morals, advice and motivation. so that it is effectively used as a teaching strategy. The teaching strategy of geguritan through communicative methods assisted by the media of dolanan cublak-cublak suweng contains four elements of language skills, namely listening skills, which are obtained from the introduction of geguritan and the media of dolanan songs which affect the cognitive abilities and listening power of students, writing skills obtained from writing the meaning of dolanan songs that affect students' writing procedures, reading skills obtained from reading the results of the meaning of dolanan songs that affect the level of further reading comprehension of students, and speaking skills obtained from group discussions and performances of singing dolanan songs that affect speaking ability and courage of students, this teaching strategy has many benefits and is effectively applied to other students.